Anion coordinated capsules and pseudocapsules of tripodal amide, urea and thiourea scaffolds - Dey, Sandeep Kumar; Basu, Arghya; Chutia, Romen; Das, Gopal (RSC Advances, 2016)
This review aims to deliver a detailed and comparative account of the reported examples of anion (halide and oxyanions) coordinated capsules and pseudocapsules of tripodal receptors that employ hydrogen bonds and/or electrostatic hydrogen bonds offered by specific binding sites from amide, urea and thiourea functionalities. The review discusses both the structural aspects of anion binding and solution-state anion binding affinities of N-bridged and aryl-bridged tripodal receptors. Discussions relating to selective anion recognition and separation, carbondioxide uptake, and transmembrane anion transport, as demonstrated by some of these tripodal receptors have also been included in this review.